Corneal Nerve Morphology and Tear Film Substance P in Diabetes. Issue 7 (July 2017) - Markoulli, Maria; You, Jingjing; Kim, Juno; Duong, Carmen L.; Tolentino, Jonathan B.; Karras, Joshua; Lum, Edward
ABSTRACT: Purpose: This work aims to characterize the relationship between tear film neuropeptide substance P and the structural integrity of the sub-basal nerve plexus in diabetes. Methods: Seventeen healthy control participants and nine participants with diabetes were recruited in this cross-sectional study. Total protein content and substance P concentrations were determined in the flush tears of participants. Corneal nerve morphology was assessed by capturing the corneal sub-basal nerve plexus using the Heidelberg Retinal Tomograph II with the Rostock Corneal Module (Heidelberg Engineering GmbH, Heidelberg, Germany) in the central cornea. Corneal nerve fiber density (CNFD) was measured using ACCMetrics (M.A. Dabbah, Imaging Science and Biomedical Engineering, Manchester, UK) on eight captured images. Comparisons between groups were made using independent samples t-tests. Correlations between parameters were analyzed using Pearson's correlations. Results: Substance P concentrations were significantly higher in the tears of the control group compared to participants with diabetes (4150 ± 4752 and 1473 ± 1671 pg/mL, respectively, P = .047). There was no significant difference in total protein content between the groups (3.4 ± 1.8 and 2.6 ± 1.7 mg/mL in the control and diabetes groups, respectively, P = .262). CNFD was significantly lower in the participants with diabetes compared to the control group (16.1 ± 5.7 and 21.5 ± 7.0 mm/mm 2, respectively, P = .041). There was a moderate correlation between substance P and CNFD ( r = 0.48, P = .01). Conclusions: Substance P is expressed at a significantly lower level in the tears of people with diabetes compared with healthy controls. The positive correlation between substance P and corneal nerve density indicates that substance P may be a potential biomarker for corneal nerve health.